2016
DOI: 10.1093/mnras/stw2995
|View full text |Cite
|
Sign up to set email alerts
|

Towards self-consistent modelling of the Sgr A* accretion flow: linking theory and observation

Abstract: The interplay between supermassive black holes (SMBHs) and their environments is believed to command an essential role in galaxy evolution. The majority of these SMBHs are in the radiative inefficient accretion phase where this interplay remains elusive, but suggestively important, due to few observational constraints. To remedy this, we directly fit 2D hydrodynamic simulations to Chandra observations of Sgr A* with Markov chain Monte Carlo sampling, self-consistently modelling the 2D inflowoutflow solution fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 42 publications
(130 reference statements)
2
37
0
Order By: Relevance
“…Extend this to our understanding of SgrA * , with the fiducial Bondi radius of 3 7 (Wang et al 2013). The brightness from the inner scattering halo is comparable to the fraction of quiescent SgrA * flux that has been attributed to unresolved flares (10%, Neilsen et al 2013) and to point-like emission (4%, Roberts et al 2017). …”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Extend this to our understanding of SgrA * , with the fiducial Bondi radius of 3 7 (Wang et al 2013). The brightness from the inner scattering halo is comparable to the fraction of quiescent SgrA * flux that has been attributed to unresolved flares (10%, Neilsen et al 2013) and to point-like emission (4%, Roberts et al 2017). …”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, the ISM column obtained from X-ray absorption does not match that obtained from extinction measurements in the infrared (Fritz et al 2011); they differ by a factor of two. Finally, Chandra observations have revealed that the X-ray emission from SgrA * is extended, allowing us to test theoretical models that trace the flow of hot gas as it falls into the supermassive black hole (Baganoff et al 2003;Shcherbakov & Baganoff 2010;Wang et al 2013;Roberts et al 2017). This situation is complicated by the fact that SgrA * is variable, flaring on the order of once per day for hours at a time (e.g., Neilsen et al 2013) and impacting neutral gas in the vicinity of the GC (e.g., Krivonos et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, most of the material accreting through the Bondi radius must be ejected in an outflow of some kind (e.g., Sadowski et al 2013;Yuan & Narayan 2014;Yuan et al 2015;Roberts et al 2017). Both jets and broadly collimated winds have been considered, but the nature of the outflow remains to be observationally determined.…”
Section: Discussionmentioning
confidence: 99%
“…Could such a radiatively inefficient IMBH explain the possible point-like component of the X-ray emission? In the hot accretion case, the spatial distributions of the plasma density and temperature of the accretion flow can be scaled with their values at the so-called Bondi radius r b ∝ M IMBH (e.g., Roberts et al 2017). This radius characterizes the size of the region in which the plasma of certain thermal and/or kinematic properties can be initially captured by the gravity of the black hole.…”
Section: Constraints On X-ray Emission From the Putative Imbhmentioning
confidence: 99%
“…This radius characterizes the size of the region in which the plasma of certain thermal and/or kinematic properties can be initially captured by the gravity of the black hole. Although the Bondi accretion model itself is typically too simplistic to describe the complex accretion process, the X-ray emission from the hot gas accretion is qualitatively dominated by the outer accretion flow (e.g., Wang et al 2013;Roberts et al 2017). One may then expect that L x ∝ r 3 b n 2 e ∝ M 3 IMBH n 2 e .…”
Section: Constraints On X-ray Emission From the Putative Imbhmentioning
confidence: 99%